2015
DOI: 10.3390/microorganisms3040903
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Select Agents to Predation by Predatory Bacteria

Abstract: Select Agents are microorganisms and toxins considered to be exploitable as biological weapons. Although infections by many Select Agents can be treated by conventional antibiotics, the risk of an emerging or engineered drug resistant strain is of great concern. One group of microorganisms that is showing potential to control drug resistant Gram-negative bacteria are the predatory bacteria from the genera Bdellovibrio spp. and Micavibrio spp. In this study, we have examined the ability of Bdellovibrio bacterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…In this study, we have found no change in the ability of M. aeruginosavorus to prey on S. marcescens mutants defective in the production of prodigiosin and phospholipase-A. This finding is in accord with the fact that M. aeruginosavorus is able to attack other human pathogens, which are known to secrete a variety of toxins and antimicrobials, such as Burkholderia mallei, P. aeruginosa and Yersinia pestis 6 9 , 11 . An additional virulence factor that is produced by S. marcescens K904 are metalloproteases which are members of the RTX-toxin family 36 , 37 and were shown to be cytotoxic to mammalian cells in vitro 36 , 38 , 39 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, we have found no change in the ability of M. aeruginosavorus to prey on S. marcescens mutants defective in the production of prodigiosin and phospholipase-A. This finding is in accord with the fact that M. aeruginosavorus is able to attack other human pathogens, which are known to secrete a variety of toxins and antimicrobials, such as Burkholderia mallei, P. aeruginosa and Yersinia pestis 6 9 , 11 . An additional virulence factor that is produced by S. marcescens K904 are metalloproteases which are members of the RTX-toxin family 36 , 37 and were shown to be cytotoxic to mammalian cells in vitro 36 , 38 , 39 .…”
Section: Discussionsupporting
confidence: 80%
“… 4 in a study in which the epibiotic predators M. aeruginosavorus ARL-13 and strain EPB were compared to an additional epibiotic predator Bdellovibrio exovorus JSS and two periplasmic predators Bdellovibrio bacteriovorus HD100 and B. marinus SJ. Further studies focused on the prey range of M. aeruginosavorus 6 9 , its potential use as a live antibiotic to control infection 10 , its ability to prey on drug resistant pathogens and biofilms 6 , 11 , 12 , and the predator’s non-toxic attributes when exposed to mammalian cells lines in vitro 8 , 13 . Additional studies demonstrated the predators’ non-pathogenic characteristics using several animal infection models including rabbit eye wound infection models 14 , mice and rat intranasal and intravenous inoculation models 15 17 , and gastrointestinal inoculation models used to measure the impact on gut bacterial microbiota 18 .…”
Section: Introductionmentioning
confidence: 99%
“…S7 and S8. (23)(24)(25)(26). Here, we show that BALOs are able to prevent bacterial infections in plant tissues.…”
Section: Discussionmentioning
confidence: 61%
“…Although the exploration of the therapeutic potential of BALOs for medicine has dramatically increased in the past years, showing that BALOs can curb infections in vivo (23)(24)(25)(26), few studies have explored their potential against phytopathogens (27)(28)(29). The aim of this study was to assess the efficiency of B. bacteriovorus against potato rot bacteria.…”
mentioning
confidence: 99%
“…Gram-positive bacterial biofilms induce an intracellular transcriptome response in B. bacteriovorus , leading to the secretion of several proteases, hydrolases, and nucleases, which is associated with the degradative effect of BALOs on Gram-positive bacterial biofilms (Im et al, 2018 ; Bratanis et al, 2020 ). in vivo animal models have demonstrated that predatory bacteria are nontoxic and nonimmunogenic in rodents (Russo et al, 2015 ), while in vitro predatory bacteria are nonpathogenic and nontoxic to several kinds of human cell lines (Gupta et al, 2016 ). Despite the limitations of predatory bacteria, such as their potentially negative effect on the natural microbiota of the body and their incomplete predation of prey bacteria (Shatzkes et al, 2017 ), these bacteria are still regarded as “living antibiotics,” and researchers hope that these bacteria can serve alternatives to traditional antibiotics.…”
Section: Strategies Against Microbial Biofilmsmentioning
confidence: 99%